Tinospora Cordifolia (Gurjo) and Its Potential Role to Combat with COVID-19: A Review - Subedi, Manisha; Timilsina, Binita; Adhikari, Neetu; Gautam, Deepak (Janapriya Journal of Interdisciplinary Studies, 2022)
Plant-based medicines have been used to maintain health and treat disease since the dawn of civilization. The present review focuses on studies that have been done on the characteristics of T. cordifolia to see if they may be used to combat COVID-19 Pandemic. During the review, various methodological activities were involved from developing the review concept, reviewing the articles, analyzing them, and finally writing the paper. The result shows that herbal medicine is used by 80% of the world’s population for some aspect of basic health care. T. cordifolia is a medicinal plant which is a useful home remedy for chronic fever, as it calms burning sensations and boosts energy and hunger. Glycosides, alkaloids, steroids, diterpenoid lactones, sesquiterpenoid, and aliphatic chemicals are the most common substances found in this herb. Scientific research on this medicine could lead to a novel method as well as knowledge into COVID-19 prevention, management, and the development of a new therapeutic component.